A critical discourse analysis of media political bias on Marvel’s Sabra controversy - Imani, Aurelia Puti; Wahyudi, Ribut (Englisia Journal, 2025)
Online news media often employ language manipulation to favor specific parties, potentially reflecting political bias, particularly in coverage of controversial issues. One such issue is Marvel’s Sabra, an Israeli Mossad superhero character, whose inclusion sparked controversy due to its association with the 1982 Sabra and Shatila massacre in Lebanon. This study investigates indications of political bias in media portrayals of the Sabra controversy. Data were sourced from six online news articles published by Al Jazeera and The Times of Israel between September and October 2022, addressing Marvel’s Sabra, alongside articles from the same period in prior years commemorating the 1982 massacre. The analysis utilized Critical Discourse Analysis (CDA) to examine ideological underpinnings through text structures and Political Discourse Analysis (PDA) to assess practical arguments. Findings revealed contrasting narratives: Al Jazeera opposed Sabra’s depiction, viewing it as propagandistic and linked to Israel’s alleged role in the massacre, while The Times of Israel supported the character, asserting Israel’s lack of direct responsibility for the event.